2009
DOI: 10.1007/s10290-009-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

On the bilateral trade effects of free trade agreements between the EU-15 and the CEEC-4 countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
1
33
0
1
Order By: Relevance
“…Econometric studies assessing the impact of trade policies on trade have found evidence of endogeneity for the trade policy variable (Lederman andÖzden 2004;Baier and Bergstrand 2007;Caporale et al 2009). Intuitively, simultaneity between FDI and tariffs may arise if closer relations in terms of investments between the two countries affect the level of bilateral tariffs.…”
Section: Data and Econometric Issuesmentioning
confidence: 98%
“…Econometric studies assessing the impact of trade policies on trade have found evidence of endogeneity for the trade policy variable (Lederman andÖzden 2004;Baier and Bergstrand 2007;Caporale et al 2009). Intuitively, simultaneity between FDI and tariffs may arise if closer relations in terms of investments between the two countries affect the level of bilateral tariffs.…”
Section: Data and Econometric Issuesmentioning
confidence: 98%
“…In addition, there exists an extensive literature on the effects of regional integration on trade flows. Most studies are based on Viner's () framework and analyze the dynamic effects of geographical size, industry location, and economies of scale (see, e.g., Caporale, Rault, Sova, & Sova, ). Viner shows that a move to free trade between two countries that maintain their respective external tariffs toward the rest of the world could leave both countries worse off.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such effects have been quantified by applying the well-known gravity equation for international trade data, the right-hand side of which includes FTA dummy variables that take unity if trading partners belong to the same FTA and zero otherwise (e.g., Baier and Bergstrand 2007;Caporale et al 2009;Medvedev 2010;Roy 2010;and Vicard 2009). In this sort of analyses, the coefficient for the FTA dummy represents total trade creation effects of FTAs, which are often proved to be significantly positive.…”
mentioning
confidence: 99%